EKSISTENSI KOMISIONER PEREMPUAN DALAM MEWUJUDKAN KESETARAAN GENDER PADA KPU PROVINSI DAN KABUPATEN/KOTA DI SUMATERA BARAT - Novita, Irma; ', Jendrius; Adnan, Fachri; Handoko, Tito (Universitas Riau, 2018)
The institution of Election organizers such as the General Election Commission is tasked with implementing the electoral stages process. Placing women in the election field is not only a matter of equality with men but part of the effort to encourage women?s political participation. The involvement of women as election organizers will play a major role in maximizing women?s participation in the elections. The main act women can take as election organizers at each stage is to ensure that women?s needs are considered and incorporated into programs or policies that are properly designed and implemented. The results of the number of women commissioners as election organizers are still minimal quantitatively. And if you look at the composition of the current membership structure, this women commissioner is still very minimal due to the 30 percent quota has not been fulfilled so there is still discrimination and many obstacles and challenges are found in realizing gender equality and women?s opportunities are limited in performing the tasks of elections. Most of these commissioners also feel there is still gender inequality. Challenges and obstacles such as social barriers in the form of Patriarchal Culture that still exist in Minangkabau society are still felt even though it is not as thick as in past times. In addition, stereotypes, marginalization, subordination, and the double burden also greatly affect the existence of this women commissioner in realizing gender equality.